Single Nucleoprotein Residue Modulates Arenavirus Replication Complex Formation - Knopp, Kristeene A.; Ngo, Tuan; Gershon, Paul D.; Buchmeier, Michael J. (mBio, 2015)
The Arenaviridae are enveloped, negative-sense RNA viruses with several family members that cause hemorrhagic fevers. This work provides immunofluorescence evidence that, unlike those of New World arenaviruses, the replication and transcription complexes (RTC) of lymphocytic choriomeningitis virus (LCMV) colocalize with eukaryotic initiation factor 4E (eIF4E) and that eIF4E may participate in the translation of LCMV mRNA. Additionally, we identify two residues in the LCMV nucleoprotein (NP) that are conserved in every mammalian arenavirus and are required for recombinant LCMV recovery. One of these sites, Y125, was confirmed to be phosphorylated by using liquid chromatography-tandem mass spectrometry (LC-MS/MS). NP Y125 is located in the N-terminal region of NP that is disordered when RNA is bound. The other site, NP T206, was predicted to be a phosphorylation site. Immunofluorescence analysis demonstrated that NP T206 is required for the formation of the punctate RTC that are typically observed during LCMV infection. A minigenome reporter assay using NP mutants, as well as Northern blot analysis, demonstrated that although NP T206A does not form punctate RTC, it can transcribe and replicate a minigenome. However, in the presence of matrix protein (Z) and glycoprotein (GP), translation of the minigenome message with NP T206A was inhibited, suggesting that punctate RTC formation is required to regulate viral replication. Together, these results highlight a significant difference between New and Old World arenaviruses and demonstrate the importance of RTC formation and translation priming in RTC for Old World arenaviruses. IMPORTANCE Several members of the Arenaviridae cause hemorrhagic fevers and are classified as category A pathogens. Arenavirus replication-transcription complexes (RTC) are nucleated by the viral nucleoprotein. This study demonstrates that the formation of these complexes is required for virus viability and suggests that RTC nucleation is regulated by the phosphorylation of a single nucleoprotein residue. This work adds to the body of knowledge about how these key viral structures are formed and participate in virus replication. Additionally, the fact that Old World arenavirus complexes colocalize with the eukaryotic initiation factor 4E, while New World arenaviruses do not, is only the second notable difference observed between New and Old World arenaviruses, the first being the difference in the glycoprotein receptor. Several members of the Arenaviridae cause hemorrhagic fevers and are classified as category A pathogens. Arenavirus replication-transcription complexes (RTC) are nucleated by the viral nucleoprotein. This study demonstrates that the formation of these complexes is required for virus viability and suggests that RTC nucleation is regulated by the phosphorylation of a single nucleoprotein residue. This work adds to the body of knowledge about how these key viral structures are formed and participate in virus replication. Additionally, the fact that Old World arenavirus complexes colocalize with the eukaryotic initiation factor 4E, while New World arenaviruses do not, is only the second notable difference observed between New and Old World arenaviruses, the first being the difference in the glycoprotein receptor.